Liver‐Targeted Toll‐Like Receptor 7 Agonist Combined With Entecavir Promotes a Functional Cure in the Woodchuck Model of Hepatitis B Virus. Issue 10 (8th July 2019) - Korolowizc, Kyle E.; Li, Bin; Huang, Xu; Yon, Changsuek; Rodrigo, Evelyn; Corpuz, Manny; Plouffe, David M.; Kallakury, Bhaskar V.; Suresh, Manasa; Wu, Tom Y.‐H.; Miller, Andrew T.; Menne, Stephan
Abstract : Current therapeutics for chronic infection with hepatitis B virus (HBV) rarely induce functional cure due to the immunotolerant status of patients. Small molecule agonists targeting toll‐like receptor 7 (TLR7) have been shown to elicit a functional cure in animal models of HBV but sometimes with poor tolerability due to immune‐related toxicities. In an effort to increase the therapeutic window of TLR7 agonists to treat chronic hepatitis B (CHB), we developed an oral TLR7 agonist, APR002, designed to act locally in the gastrointestinal tract and liver, thus minimizing systemic exposure and improving tolerability. Here, we describe the pharmacokinetic/pharmacodynamic (PK/PD) profile of APR002 in mice and uninfected woodchucks as well as the safety and antiviral efficacy in combination with entecavir (ETV) in woodchucks with CHB. Treatment of woodchucks chronically infected with woodchuck hepatitis virus (WHV) with weekly oral doses of APR002 was well‐tolerated. While APR002 and ETV single agents did not elicit sustained viral control, combination therapy resulted in durable immune‐mediated suppression of the chronic infection. These woodchucks also had detectable antibodies to viral antigens, enhanced interferon‐stimulated gene expression, and loss of WHV covalently closed circular DNA. Conclusion: APR002 is a novel TLR7 agonist exhibiting a distinct PK/PD profile that in combination with ETV can safely attain a functional cure in woodchucks with chronic WHV infection. Our results support further investigation of liver‐targeted TLR7 agonists in human CHB. Abstract :